Philosophers on consciousness : talking about the mind - Symes, Jack (London [England] : Bloomsbury Academic, 2022)
"We know, more intimately than anything else, what it's like to undergo a rich world of experiences: agonizing pains, dizzying pleasures, heady rage and existential doubts. But, despite the incredible advances of physical science, it seems that we're no closer to an explanation of how this inner world of experiences comes about. No matter how detailed our description of the physical brain, perhaps we'll always be left with this same question: how and why does the brain produce consciousness? This book is a short, accessible and engaging guide to the mystery of consciousness. Featuring remastered interviews and original essays from the world's leading thinkers, Philosophers on Consciousness sheds new light on the most promising theories in philosophy and science. Beyond understanding the mind, this is a journey into personal identity, the origin of meaning, the nature of morality and the fundamental structure of reality"
Contributors -- Illustration -- Acknowledgements -- Preface -- 1. -- Why Consciousness Matters, Gregory Miller -- 2. -- The Grand Illusion, Susan Blackmore -- 3. -- The Hard Problem, David Chalmers -- 4. -- A Change of Heart, Frank Jackson -- 5. -- The Given, Michelle Montague -- 6. -- A Biologist's Perspective, Massimo Pigliucci -- 7. -- The Hornswoggle Problem, Patricia Churchland -- 8. -- Illusionism, Keith Frankish -- 9. -- Closing the Theatre, Daniel Dennett -- 10. -- The Denial, Galen Strawson -- 11. -- Galileo's Error, Philip Goff -- 12. -- The World as Consciousness, Miri Albahari & Jack Symes -- Notes & Sources -- Index
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Consciousness; Philosophy of mind; Philosophy of mind,Popular philosophy; Electronic books